Effects of different vibration frequencies on spinal cord reflex circuits and thermoalgesic perception - (:unkn) unknown (JMNI, 2021)
Objectives: We studied the effect of different vibration frequencies on spinal cord excitability and heat pain perception. We hypothesized that the effects of vibration on spinal cord reflexes, and, also those on heat pain perception, depend on vibration frequency. Methods: In 9 healthy subjects, we applied vibration over the tibial is anterior muscle at three different frequencies (50, 150, or 250 Hz) on spinal cord reflex excitably, tested with the H reflex and the T wave in the soleus muscle, as well as on sensory and pain perception. tested by measuring warm perception (WT) and heat pain perception thresholds, (HPT) in sites rostra! and caudal to vibration. Exams were carried out before, during, and after vibration. Results: The amplitude of the H reflex and T wave significantly decreased during vibration in comparison to baseline. Low frequencies (50 and 150Hz) induced greater reflex suppression than high frequency (250Hz). No significant changes were observed on WT and HPT. Conclusions: The effects of vibratory stimulation can be summarized as frequency-related suppression of the spinal cord excitability without an effect on warm and heat pain perception. The present results may help to design vibration-related interventions intended to diminish spinal cord reflex excitability in spastic patients.
Keywords: Heat Pain Perception; Lower Limbs; Spinal Cord Reflex Circuits; Vibration Frequencies; Warm Perception; CUTANEOUSLY APPLIED VIBRATION; FOCAL MUSCLE VIBRATION; UPPER-LIMB SPASTICITY; POSTSTROKE PATIENTS; EVOKED-POTENTIALS; PAIN MECHANISMS; DORSAL-HORN; TENDON; EXCITABILITY; RESPONSES